EFFECTIVENESS OF PHYSICAL THERAPY AND OCCUPATIONAL THERAPY ON MOTOR FUNCTION RECOVERY IN STROKE PATIENTS: A SYSTEMATIC REVIEW - Dimas Hadi Prayoga; Sujarwadi, Mokh.; Zuhroidah, Ida; Toha, Mukhammad; Zahra, Fatimah; Laili, Nadia Rohmatul; Rahmawati, Apriana (Journal of Nursing and Midwifery Sciences, 2025)
Stroke continues to be a leading cause of long-term disability and the most common and disabling of such disabilities is motor impairments. Return of motor function is essential to independence in activities of daily living. Intensive physical and occupational therapy are applied widely to promote neuroplasticity and motor response; however, there is a scarcity of evidence on their effectiveness. To review Effectiveness of Physical Therapy and Occupational Therapy on Motor Function Recovery in Stroke Patients . The research methodology used in this study is systematic review. A systematic search was undertaken in major databases, for the period 2019-2025. Included trials were randomised controlled trials of physical, occupational therapy, or combined interventions in adult stroke patients with assessment of motor outcome by standardised instruments. Narrative synthesis was undertaken and results were summarised by type of intervention. Fifteen studies met inclusion criteria which included robot-assisted training, mirror therapy, task-oriented training, exoskeleton-based therapy, and virtual reality. Most interventions were significantly better than conventional therapy or usual care in terms of upper extremity motor function, daily activity independence, and quality of life. When delivered at subacute and with sufficient intensity, technology-assisted or combined approaches yielded greater benefit. Physical and occupational therapy are very important for motor recovery after a stroke. Recent evidence for the integration of task-oriented, mirror-based, and technology-assisted approaches into rehabilitation is reviewed for their potential to maximise functional outcome. More high-quality research is needed to determine when, how much and how to combine therapies.